PEMANFAATAN PEMAHAMAN BUDAYA SEBAGAI DASAR PENGUASAAN KESANTUNAN DALAM PENDIDIKAN BAHASA - MARDIYAH, MARDIYAH (Universitas Islam Negeri Raden Intan Lampung, 2014)
This article reviews the aspects of cultural understanding as used the mastery of the politeness in the language education. These all cultural understanding, mastery of politeness, and language education should be integrated by the teacher in the learning situation both inside and outside of the classroom. Both the social amenity and the food are good for beginning to achieve the mastery of politeness in a community culture or in the cross-cultural society. Language is a communication device between a member of social group and others. It is Important to maintain the social relation. Politeness cannot be mastered without the real activity in the language used dally.